Differential MMP-2 and MMP-9 Activity and Collagen Distribution in Skeletal Muscle from pacu (Piaractus mesopotamicus) During Juvenile and Adult Growth Phases - Michelin, Aline Cristina [UNESP] (2009)
Here, we evaluated collagen distribution and matrix metalloproteinases (MMPs) MMP-2 and MMP-9 activities in skeletal muscle of pacu (Piaractus mesopotamicus) during juvenile and adult growth phases. Muscle samples from juvenile and adult fishes were processed by histochemistry for collagen system fibers and for gelatin-zymography for MMP-2 and MMP-9 activities analysis. Picrosirius staining revealed a myosept, endomysium, and perimysium-like structures in both growth phases and muscle types, with increased areas of collagen fibers in adults, mainly in red muscle. Reticulin staining showed that reticular fibers in the endomysium-like structure were thinner and discontinuous in the red muscle fibers. The zymography revealed clear bands of the pro-MMP-9, active-MMP-9, intermediate-MMP-2, and active-MMP-2 forms in red and white muscle in both growth phases. MMP-2 activity was more intense in juvenile than adult muscle fibers. Comparing the red and white muscle types, MMP-2 activity was significantly higher in red muscle in adult phase only. The activity of MMP-9 forms was similar in juvenile red and white muscles and in the adult red muscle, without any activity in adult white muscle. In conclusion, our results show that, in pacu, the higher activities of MMP-2 and -9 are associated with the rapid muscle growth in juvenile age and in adult fish, these activities are related with a different red and white muscle physiology. This study may contribute to the understanding muscle growth mechanisms and may also contribute to analyse red and the white muscle parameters of firmness and softness, respectively, of the commercial product. Anat Rec, 292:387-395, 2009. (C) 2009 Wiley-Liss, Inc.